1987
DOI: 10.1002/art.1780300808
|View full text |Cite
|
Sign up to set email alerts
|

Association of a 9.2‐kilobase pvu ii class i major histocompatibility complex restriction fragment length polymorphism with ankylosing spondylitis

Abstract: We analyzed DNA restriction fragment length polymorphism (RFLP) in 53 white ankylosing spondylitis (AS) patients and 92 healthy controls, utilizing a full-length HLA-B7 complementary DNA probe. A 9.2-kilobase (kb) Pvu I1 fragment was found to be significantly increasexn frequency in B27 positive AS patients compared with the B27 positive control group (P = 0.00085, relative risk = 7.2). The presence of both B27 and the 9.2-kb RFLP in an individual conferred a relative risk for AS of 297, compared with a relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
2

Year Published

1988
1988
1993
1993

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 21 publications
(8 reference statements)
0
8
2
Order By: Relevance
“…Genomic DNA was extracted from peripheral blood leukocytes (18) and 10 ug digested with the restriction endonucleases Bam HI and Taq I under conditions specified by the manufacturer, and then electrophoresed through 0.8% agarose gel overnight at 50 V. The gel was then stained in ethidium bromide, photographed, and subjected to denaturation and neutralization as described previously (19), and transferred onto Zetabind membranes (Cuno Inc., Meriden, CT).…”
Section: Methodsmentioning
confidence: 99%
“…Genomic DNA was extracted from peripheral blood leukocytes (18) and 10 ug digested with the restriction endonucleases Bam HI and Taq I under conditions specified by the manufacturer, and then electrophoresed through 0.8% agarose gel overnight at 50 V. The gel was then stained in ethidium bromide, photographed, and subjected to denaturation and neutralization as described previously (19), and transferred onto Zetabind membranes (Cuno Inc., Meriden, CT).…”
Section: Methodsmentioning
confidence: 99%
“…"Broad" HLA-DR specificities (DR1, DR2, DR3/6, DR4, DR5(DRwll), DR5(DRwl2), DR7, DRw8, DR9, and DRw1O) were determined either by RFLP analysis of Taq I, Bam HI and Eco RI digested genomic DNA described previously (42) or by polymerase chain reaction (PCR) amplification of 0.5 gg of genomic DNA using the primers DRBAMP-A (5'-CCCCACAGCACGTTTCTTG-3') and DRBAMP-B (5'-CCGCTGCACTGTGAAGCTCT-3'). The PCR was carried out for 30 cycles under the following parameters: denaturation 1 min at 96°C, annealing I min at 55°C, extension 2 min at 72°C.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of studies have reported associations of SS with class I MHC specificities, includingHLA-A9 (11,12), B8 (13,14), andB35 (15,16); class II MHC, including HLA-DRl (16)(17)(18)(19), DR3 (14,20) and DR5 (19,(21)(22)(23); and class III MHC, specifically C4 null alleles (15,22). These associations have been generally weak and inconsistent between different centers, and some investigations have even been unable to show any significant HLA associations with SS (24)(25)(26)(27)(28) (33); 10 sg was digested with the restriction endonucleases BamH 1 and TaqI under conditions specified by the manufacturer, and then electrophoresed through an 0.8% agarose gel overnight at 50 V. The gel was then stained in ethidium bromide, photographed, subjected to denaturation and neutralization as described previously (34), and then transferred on to Zetabind membranes. (Cuno, Inc., Meriden, CT).…”
mentioning
confidence: 99%
“…Oligonucleotide probes corresponding to the polymorphisms at positions 25,34,55, and 69 were used forthe hybridizations as supplied by the 11th International Histocompatibility Testing Workshop.…”
mentioning
confidence: 99%